Kształtowanie legislacji Unii Europejskiej na przykładzie problematyki GMO - Gąsowski, Andrzej (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2012)
The paper presents an analysis of the process of shaping European Union legislation on GMO’s. Describes impact on the legislative process by the most important of the EU institutions: the Commission, the Council and the European Parliament as well as by various lobbing groups. The complexity and partial openness of the Union’s legislative process introduced in Lisbon Treaty was seen as an opportunity for consulting various Union’s social groups. As demonstrated in the work, existing system allows organized groups to delay substantially or even reject proposed changes in the EU legislation, important from the point of maintaining the global competitiveness of the European Union.